Recurrent Esophageal Stricture in a Child Post Steven-Johnson Syndrome: A Case Report - Rahman, Himawan Aulia; Astuti, Sri Kesuma; Kadim, Muzal (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Esophageal stricture is an abnormal narrowing of the esophageal lumen, resulting in dysphagia. Despite its rarity, this condition could be caused by various etiologies, including Steven-Johnson Syndrome (SJS). In some cases, stricture could recur, which complicates the management. This case report presented a rare case of refractory esophageal stricture in children with Steven-Johnson Syndrome. Case: A 5-years-old boy with a prior history of SJS presented with dysphagia for one month. The patient experienced choking, blood vomiting, stomatitis, swelling on the lips, and difficulty in swallowing solid food. Barium meal and EGD test confirmed the diagnosis of esophageal strictures. The patient then underwent dilation using bougie dilator. However, he continued to experience dysphagia, resulting in a total of 15 serial dilation sessions. Discussion: Esophageal dysphagia is observed in patients who experience difficulty swallowing solid food. SJS can contribute to the development of esophageal dysphagia by causing inflammation of the esophageal mucosa, resulting in lesions and strictures. In patients with esophageal strictures, two types of dilation methods are available: bougie dilator with wire guidance (Savary-Gilliard) and balloon dilator, with the current consensus for dilation procedures supporting the rule of three. For patients with refractory strictures, other modalities such as mitomycin-C injection and stent placement are also available. Esophageal replacement surgery is considered as the last resort for refractory stricture patients who have not responded to previous treatments. Conclusion: Steven-Johnson Syndrome is a rare cause of esophageal strictures. The management of refractory esophageal stricture requires a comprehensive subspecialty care and long-term monitoring.